Secrets of lost empires. Inca [videorecording (DVD)] - Barnes, Michael (WGBH Boston Video, 2006)
Television program that explores the Inca civilization from the perspective of their construction techniques. Archaeological teams use traditional building techniques to test their hypotheses, including the building of a 150-foot suspension bridge using nothing but grass.